Pasando páginas : la historia de mi vida - Sotomayor, Sonia, 1954-; Delacre, Lulu; Mlawer, Teresa (New York, NY : Philomel Books, 2018)
"A Spanish translation of the picture book autobiography of Sonia Sotomayor, Turning Pages"--
LC copy 1 signed by author.
Keywords: Sotomayor, Sonia, -- 1954- -- Juvenile literature; United States. -- Supreme Court -- Officials and employees -- Biography -- Juvenile literature; Hispanic American judges -- Biography -- Juvenile literature; Judges -- United States -- Biography -- Juvenile literature; JUVENILE NONFICTION / Biography & Autobiography / Political; JUVENILE NONFICTION / Biography & Autobiography / Women; JUVENILE NONFICTION / People & Places / United States / Hispanic & Latino